Phase-change cooling of lithium-ion battery using parallel mini-channels cold plate with varying flow rate. (May 2023) - Ren, Honglei; Yin, Liaofei; Dang, Chao; Liu, Ruming; Jia, Li; Ding, Yong
Abstract: In this study, a liquid phase-change cooling module with mini-channels cold plate was designed. The temperature properties of a battery monomer with different cooling conditions and varying discharge rates were investigated. The heat dissipation contribution of latent heat transfer to the overall cooling performance of the mini-channels cold plate was analyzed based on the outlet vapor quality. Particularly, a cooling strategy with varying coolant flow rates was proposed and examined at 3C discharge rate. The results illustrated that the designed battery cooling module had an ideal effect on lowering the battery's surface temperature and increasing the battery's temperature uniformity. Compared to the cooling strategy with constant coolant flow rate, the proposed variable flow cooling strategy better matched the dynamic law of battery heat generation and increased the contribution of the latent heat transfer to the battery cooling, thereby efficiently reducing the coolant consumption and the pump power consumption of the BTMS (battery thermal management system) while providing the same or even superior cooling performance. The findings could assist the optimization of the BTMS and be the reference for the application of the varying flow rate cooling strategy in actual engineering.